PEMBERDAYAAN GURU SD DALAM PEMBUATAN BUKU BERBASIS KEARIFAN LOKAL INDRAGIRI HULU - Alpusari, Mahmud; Copriady, Jimmi; Anggriani, Mitha Dwi; Marhadi, Hendri; Erlisnawati, Erlisnawati; Guslinda, Guslinda; Fatmawilda, Fatmawilda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Efforts to empower elementary school teachers through socialization and training activities for making local wisdom-based books were carried out at SDN 021 Air Molek, Air Molek II Village, aiming to improve teachers' skills in designing and creating books that integrate the local wisdom of Indragiri Hulu Regency. The training method included theoretical sessions on local wisdom, writing techniques, and book design, as well as hands-on practice in book preparation. The results of the training showed an increase in teachers' skills, with three books published discussing the culture of surat kapal, the history of gibaga, and the history of kembang harum. Participants showed great enthusiasm and applied the new knowledge in their work. However, there were challenges related to a lack of experience among some teachers in book-making, which requires continued support and training. The implications of these findings suggest that with improvements in support and training, this activity has the potential to have a greater positive impact on the quality of education and the preservation of local wisdom in the area. Improved teacher skills are expected to expand the range of locally-based teaching materials and contribute significantly to education in Indragiri Hulu district.